Surficial arsenic redistribution above gold-mineralised zones in East Otago, New Zealand. Issue 4 (2nd October 2019) - Blake, Frances; Grant, Kacee; MacKenzie, Doug; Scott, James; Craw, Dave
ABSTRACT: Groundwater-driven clay alteration of gold-mineralised Otago Schist has caused leaching and redistribution of arsenic (As). At Macraes mine in East Otago, there is a zone of alteration up to 50 m thick beneath a Cretaceous-Cenozoic regional unconformity where hydrothermal As concentrations >1000 ppm have decreased to <150 ppm. Where periglacial aeolian silt (loess) overlies mineralised Otago Schist, As has migrated in near-surface groundwater to form geochemical enrichment anomalies in loess and colluvium, with As concentrations locally as high as 500 ppm. Most As in the clay-altered basement and Pleistocene cover is closely associated with iron oxyhydroxide (HFO) and occurs as adsorbed As(V) on the HFO or as ferric arsenate minerals. However, initial As mobility was most effective as more soluble As(III) during oxidative transition from original sulphides to arsenate. Upward As migration into Pleistocene debris on the metre scale can facilitate location of gold-mineralised rocks that have been obscured by the young cover.